Reversible modulation of the redox activity in conducting polymer nanofilms induced by hydrophobic collapse of a surface-grafted polyelectrolyte - Fenoy, Gonzalo Eduardo (2018)
We present the covalent modification of a Pani-like conducting polymer (polyaminobenzylamine, PABA) by grafting of a polyelectrolyte brush (poly [2-(methacryloyloxy)-ethyl-trimethylammonium chloride], PMETAC). As PABA has extra pendant amino moieties, the grafting procedure does not affect the backbone nitrogen atoms that are implicated in the electronic structure of the conducting polymers. Moreover, perchlorate anions interact very strongly with the quaternary ammonium pendant groups of PMETAC through ion pairing. Therefore, the grafting does not only keep the electroactivity of PABA in aqueous solutions but it adds the ion-actuation properties of the PMETAC brush to the modified electrode as demonstrated by contact angle measurements and electrochemical methods. In this way, the conjugation of the electron transfer properties of the conducting polymer with the anion responsiveness of the integrated brush renders perchlorate actuation of the electrochemical response. These results constitute a rational integration of nanometer-sized polymer building blocks that yields synergism of functionalities and illustrate the potentialities of nanoarchitectonics for pushing the limits of soft material science into the nanoworld.